Health policy and public health implications of obesity in China. Issue 7 (July 2021) - Wang, Youfa; Zhao, Li; Gao, Liwang; Pan, An; Xue, Hong
Summary: China has experienced many drastic social and economic changes and shifts in people's lifestyles since the 1990s, in parallel with the fast rising prevalence of obesity. About half of adults and a fifth of children have overweight or obesity according to the Chinese criteria, making China the country with the highest number of people with overweight or obesity in the world. Assuming that observed time trends would continue in the future, we projected the prevalence of and the number of people affected by overweight and obesity by 2030, and the associated medical costs. The rising incidence of obesity and number of people affected, as well as the related health and economic consequences, place a huge burden on China's health-care system. China has made many efforts to tackle obesity, including the implementation of relevant national policies and programmes. However, these measures are inadequate for controlling the obesity epidemic. In the past decade, China has attached great importance to public health, and the Healthy China 2030 national strategy initiated in 2016 provides a historical opportunity to establish comprehensive national strategies for tackling obesity. China is well positioned to explore an effective model to overcome the obesity epidemic; however, strong commitment and leadership from central and local governments are needed, as well as active participation of all related society sectors and individual citizens. Translation: For the Chinese translation of the paper see Supplementary Materials section.